Does XBRL Adoption Constrain Earnings Management? Early Evidence from Mandated U.S. Filers - Kim, Jeong‐Bon; Kim, Joung W.; Lim, Jee‐Hae (Contemporary Accounting Research, 2019)
ABSTRACT We examine whether the use of eXtensible Business Reporting Language (XBRL) for financial reporting (i.e., interactive data submissions) reduces earnings management during the period of XBRL implementation by the SEC. Using a sample of mandated XBRL filers, we compare the magnitude of absolute discretionary accruals in the XBRL adoption quarters with that in the non‐adopting quarters. We also take advantage of staggered (three‐stage phase‐in) XBRL implementations to perform difference‐in‐differences analyses. Our results show that absolute discretionary accruals decrease significantly from the pre‐ to the post‐XBRL period, suggesting that XBRL adoption constrains earnings management via discretionary accrual choices. Our analyses further reveal that the use of standardized official XBRL elements significantly reduces the levels of discretionary accruals, while the use of customized extension elements does not, suggesting that the former discourages accrual‐based earnings management, while the latter does not. Our results are robust to a variety of sensitivity checks.